Development of a rapid and comprehensive method for identifying organic micropollutants with high ecological risk to the aquatic environment. (January 2021) - Miyawaki, Takashi; Nishino, Takahiro; Asakawa, Daichi; Haga, Yuki; Hasegawa, Hitomi; Kadokami, Kiwao
Abstract: Currently, tens-of-thousands of chemicals are used in Japan, and their presence in and impact on aquatic ecosystems are poorly understood. Because conventional risk evaluation processes using target analysis and biological tests are time-consuming and costly, it is challenging to investigate all substances. Therefore, we aimed to develop a rapid and highly efficient screening scheme for identifying hazardous organic micropollutants (OMPs) in aquatic ecosystems. The scheme is divided into two steps: chemical analysis and risk evaluation. First, a comprehensive screening method (CSM) using gas chromatography (GC)–mass spectrometry (MS) and a database containing nearly 1000 compounds is used to identify known compounds, and nontargeted analysis is carried out using a GC × GC-time-of-flight (TOF)MS to detect compounds not registered in the database. Secondly, the predicted toxicity values obtained by quantitative structure–activity relationship (QSAR) are used to evaluate and rank the ecological risk of each detected OMPs and to identify priority compounds for detailed survey. To assess the proposed scheme, we surveyed representative urban rivers in Japan and ranked the potential toxicity of the identified compounds. The total number of compounds detected in water from each river ranged from 29 to 87, and the total concentrations ranged from 2.3 to 63 μg L −1 . Pharmaceuticals and personal care products, such as crotamiton and galaxolide, were identified in the urban rivers and found to have high ecotoxicity rankings. Thus, the scheme combining CSM and risk evaluation using QSAR is a novel screening that can identify candidates with high ecological risk in aquatic environment rapidly and efficiently. Graphical abstract: Image 1 Highlights: Organic micropollutants (OMPs) identified by targeted & nontargeted analysis. Our method (CSM) gives overall picture of OMPs pollution in the aquatic environment. Ecological risk evaluated via quantitative structure–activity relationship (QSAR). Candidate high-risk OMPs rapidly identified at low cost using CSM and QSAR. Phthalates, pharmaceuticals and personal care products priority OMPs in urban rivers in Japan.